Research Trends of Chinese-Korean Traditional Culture: A Bibliometric Analysis Based on CiteSpace. - Chen, Zhuo; Hassan, Aminuddin; Ghazali, Siti Sabihah (Pertanika Journal of Social Sciences & Humanities, 2025)
Many experts have expressed interest in the traditional culture of Chinese-Koreans; however, there has been a dearth of bibliometric analyses in this field. This study seeks to undertake a comprehensive and practical investigation into the academic status and development trends within this domain, with the findings presented in a visually accessible format. This study utilizes CiteSpace to conduct a bibliometric analysis, systematically exploring the research trends in traditional culture among Chinese-Koreans over the past two decades, with a focus on identifying hotspots, emerging trends, and key contributors. Four hundred thirty-six articles (2004--2024) from the China National Knowledge Infrastructure (CNKI) database were analyzed for publication frequency, core authors, institutions, and research frontiers. The number of annual publications fluctuates but generally showing an upward trend. Chinese-Korean traditional culture has undergone stages of germination, rapid development, and steady progress. Yanbian University, the Yanbian Party School, and the Yanbian College of Education have emerged as the primary research institutions in this field. Notably, authors such as Zhang Xiaoyu, Cui Yingjin, and Piao Tingji made significant contributions. Current research hotspots predominantly revolve around cultural inheritance, cultural identity, and rural revitalization, among others. Promoting the traditional culture of ethnic minorities is a crucial endeavor for preserving the heritage of ethnic cultures and advancing ethnic education.